2013
DOI: 10.1371/journal.pone.0065956
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput System for the Presentation of Secreted and Surface-Exposed Proteins from Gram-Positive Bacteria in Functional Metagenomics Studies

Abstract: Complex microbial ecosystems are increasingly studied through the use of metagenomics approaches. Overwhelming amounts of DNA sequence data are generated to describe the ecosystems, and allow to search for correlations between gene occurrence and clinical (e.g. in studies of the gut microbiota), physico-chemical (e.g. in studies of soil or water environments), or other parameters. Observed correlations can then be used to formulate hypotheses concerning microbial gene functions in relation to the ecosystem stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…However, B. cereus G19 and B. cereus BC-01 supplementation had no significant effect on the transcriptional level of the Aj-p105, Aj-p50, and Aj-rel genes in the mid-intestine tissue compared to those in the control group. Dobrijevic et al [65] reported that B. subtilis VI7695, a grampositive model bacterium, played a neutral in the NF-kB activation assay in human HT-29 intestine epithelial cells. Similarly, our results might also indicate that dietary B. cereus G19 and B. cereus BC-01 supplementation play a neutral role in the activation of NFkB in the intestine of sea cucumber.…”
Section: Discussionmentioning
confidence: 99%
“…However, B. cereus G19 and B. cereus BC-01 supplementation had no significant effect on the transcriptional level of the Aj-p105, Aj-p50, and Aj-rel genes in the mid-intestine tissue compared to those in the control group. Dobrijevic et al [65] reported that B. subtilis VI7695, a grampositive model bacterium, played a neutral in the NF-kB activation assay in human HT-29 intestine epithelial cells. Similarly, our results might also indicate that dietary B. cereus G19 and B. cereus BC-01 supplementation play a neutral role in the activation of NFkB in the intestine of sea cucumber.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, L. lactis MG1363 appears to be quite limited in its ability to successfully express genes from other organisms, and alternative Gram‐positive hosts (e.g. Bacillus subtilis , Dobrijevic et al ., ) may be more suitable for future functional metagenomic studies. This study does, however, also show the limitations in using E. coli as heterologous host, as the clone expressing very high activity in L. lactis MG1363 (P20A8) did not exhibit good activity in E. coli XL1 Blue.…”
Section: Discussionmentioning
confidence: 99%
“…The first of these is the expression of soluble proteins. To overcome this problem, high throughput cloning and expression methods are being developed (Dobrijevic et al , 2013, Groisillier et al, 2010, Vincentelli et al, 2011. A second challenge will be to acquire better understanding of the role of individual enzymes with the biocatalytic diversity produced by microbial communities.…”
Section: Perspectives For Enzymes In White Biotechnologymentioning
confidence: 99%